SOCIO-DEMOGRAPHIC PREDICTORS OF PRESCHOOL CHILDREN’S ACCESS TO MULTIMEDIA INTERNET CONTENT - Perevoshchikova, Nina Konstantinovna; Seliverstov, Ilya Aleksandrovich; Chernykh, Natalya Stepanovna; Shmulevich, Svetlana Aleksandrovna; Shebalina, Anastasia Olegovna; Kabanova, Kristina Vitalievna (Mother and Baby in Kuzbass, 2026)
A distinctive feature of the modern world has been the increasing influence of digital technologies on a child’s daily life. The accumulated body of data from various fields of science on the changes in the spheres of a child’s life indicates the onset of a new historical period of «Digital Childhood». The continuous and rapid development of the digital sphere creates conditions in which parents are unable to timely form a rational stance regarding a child’s interaction with a digital device – a stance capable of harmonizing the child’s development under the influence of the digital factor, on the one hand, and preventing the development of its negative consequences, on the other. The aim of the study was to analyze the association of socio-demographic predictors with the access of children in preparatory groups of preschool educational institutions to multimedia Internet materials. Materials. A total of 486 families with children aged 6-7 years were examined for an association between socio-demographic indicators and the child’s level of digital involvement. Results. The study revealed a 100% (n = 486) coverage of children by multimedia digital content (watching cartoons, listening to music, engaging with interactive offerings, etc.). Only 19,34% of children aged 6-7 years had no access to multimedia Internet content and received it offline following preliminary evaluation by parents, versus 80,65% of children with access to multimedia online content located on the Internet (df = 1, χ2 = 187,66, p < 0,001). Analysis of predictor importance revealed the greatest significance of the child-rearing style (i = 1,00) in shaping access to the Internet space. The factor of parents’ attitude towards the child’s use of digital devices demonstrated high importance (i = 0,65). The child’s sex and the type of family relationships showed moderate importance (i = 0,48 and i = 0,38, respectively). The lowest amount of screen time was noted among children without access to multimedia materials located in the web space (Me = 2 hours 36 minutes, R1 = 92,56, p1-2 < 0,001, p1-3 < 0,001). Among children with a personal digital device for accessing multimedia Internet materials, the highest screen time duration was recorded (Me = 3 hours 55 minutes, R3 = 333,20, p1-3 < 0,001, p2-3 < 0,001). Children who accessed multimedia online materials through a parent’s gadget were characterized by intermediate screen time values (Me = 3 hours 18 minutes, R2 = 199,60). Conclusion. The overwhelming majority of children aged 6-7 years have access to multimedia materials located in the Internet space. Every second child aged 6-7 years has a personal gadget for obtaining multimedia materials from the web space. The style of family upbringing is the most important predictor in shaping a child’s access to multimedia Internet materials.